2016
DOI: 10.1186/s40639-016-0020-0
|View full text |Cite
|
Sign up to set email alerts
|

Introducing compassion into the education of health care professionals; can Schwartz Rounds help?

Abstract: Whilst health care professionals embark on their careers with high ideals these can be eroded by the pressures and stress of the system. This paper explores the problems, which may lead both students and professionals, working in health care, to feel isolated and stressed. It considers the value of Schwartz Rounds as an initiative that can be used to enhance student well-being and ultimately enable students to treat each other, colleagues and patients with more compassion.Case description: Qualitative and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 7 publications
1
29
0
1
Order By: Relevance
“…In fear of shame and a punitive response, these midwives may further shy away from open disclosure and help seeking and instead, display help avoidant behaviours. Face-to-face support such as the Schwartz rounds and restorative supervision already support some midwives in work-related psychological distress (Wallbank 2010, Barker, Cornwell et al 2016). Yet for midwives seeking more private, confidential and anonymous support, the development of a targeted online intervention may now be required.…”
Section: Introductionmentioning
confidence: 99%
“…In fear of shame and a punitive response, these midwives may further shy away from open disclosure and help seeking and instead, display help avoidant behaviours. Face-to-face support such as the Schwartz rounds and restorative supervision already support some midwives in work-related psychological distress (Wallbank 2010, Barker, Cornwell et al 2016). Yet for midwives seeking more private, confidential and anonymous support, the development of a targeted online intervention may now be required.…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of Schwartz rounds (Maben et al, ) showed that they led to a greater understanding, empathy and tolerance towards both colleagues and patients. Barker, Cornwell, and Gishen () make a case for the use of Schwartz rounds within healthcare education programmes.…”
Section: Discussionmentioning
confidence: 99%
“…5) Health care workers exhibit high levels of stress and burnout and are located within health care systems which will be under increasing pressures into the future High levels of stress and burnout have been found in health care workers (Barker, Cornwell, & Gishen, 2016;Marine, Ruotsalainen, Serra, & Verbeek, 2009), including amongst the allied health professions (Chiller & Crisp, 2012;Fischer et al, 2013). There is evidence that healthcare workers experience higher levels of stress and burnout in comparison to the general workforce (Michie & Williams, 2003;Wells, 2011).…”
Section: ) There Is a Worldwide Shortage Of Health Care Workers Makimentioning
confidence: 99%
“…Health care workers, including allied health professionals, exhibit high levels of stress and burnout (Barker et al, 2016;Fischer et al, 2013). Burnout carries significant costs for the health care industry (Marine et al, 2009), is negatively associated with patient satisfaction (Fredette-Carragher, 2016), is related to increased absenteeism (Hawes, 2009) and is consistently linked to worker intention to leave (Alkorashy & Baddar, 2016).…”
Section: Implications For Workforce Well-being and Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation